2004
DOI: 10.1007/s00394-004-0515-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fat and oxidized cholesterol on gene expression in rat liver as assessed by cDNA expression array analysis

Abstract: The present study showed that dietary oxidized cholesterol transcriptionally affects many genes involved in xenobiotic metabolism and stress response--an effect that was amplified by the administration of fish oil as dietary fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Dietary PUFA greatly influence serum lipid concentrations, lipid profiles, and lipid metabolism by regulating gene expression through alteration of transcription factors involved in absorption, extracellular transport, cellular uptake, metabolism, and elimination of lipids in the animal ( Jump, 2002 ; Ringseis and Eder, 2005 ). Dietary supplementation with oxidized oil resulted in higher levels of protein carbonyl formation in blood serum ( Figure 1 ), in agreement with Zhang et al (2011b) , who reported that 5% inclusion of oxidized animal-vegetable fat in broiler diets increased plasma carbonyl content.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary PUFA greatly influence serum lipid concentrations, lipid profiles, and lipid metabolism by regulating gene expression through alteration of transcription factors involved in absorption, extracellular transport, cellular uptake, metabolism, and elimination of lipids in the animal ( Jump, 2002 ; Ringseis and Eder, 2005 ). Dietary supplementation with oxidized oil resulted in higher levels of protein carbonyl formation in blood serum ( Figure 1 ), in agreement with Zhang et al (2011b) , who reported that 5% inclusion of oxidized animal-vegetable fat in broiler diets increased plasma carbonyl content.…”
Section: Resultsmentioning
confidence: 99%
“…RNA concentration and purity were estimated from the optical density at 260 and 280 nm, respectively. cDNA synthesis and relative quantification of target gene mRNA compared to the housekeeping gene GAPDH mRNA was determined by real-time detection RT-PCR as described previously [50]. Sequences of gene-specific primers obtained from Operon (Köln, Germany) were as follows (NCBI GenBank; forward, reverse): GAPDH (NM_017008; 5'-GCA TGG CCT TCC GTG TTC C-3', 5'-GGG TGG TCC AGG GTT TCT TAC TC-3'), PPARα (NM_013196; 5'-CCC TCT CTC CAG CTT CCA GCC C-3', 5'-CCA CAA GCG TCT TCT CAG CCA TG-3'), CYP4A1 (M14972; 5'-CAG AAT GGA GAA TGG GGA CAG C-3', 5'-TGA GAA GGG CAG GAA TGA GTG G-3'), ACO (J02752; 5'-CTT TCT TGC TTG CCT TCC TTC TCC-3', 5'-GCC GTT TCA CCG CCT CGT A-3'), L-CPT I (NM_031559; 5'-GGA GAC AGA CAC CAT CCA ACA TA-3', 5'-AGG TGA TGG ACT TGT CAA ACC-3'), MCAD (NM_016986; 5'-CAA GAG AGC CTG GGA ACT TG-3', 5'-CCC CAA AGA ATT TGC TTC AA-3'), LCAD (NM_012819; 5'-AAG GAT TTA AGG GCA AGA AGC-3', 5'-GGA AGC GGA GGC GGA GTC-3'), SREBP-1c (XM_213329; 5'-GGA GCC ATG GAT TGC ACA TT-3', 5'-AGG AAG GCT TCC AGA GAG GA-3'), FAS (NM_017332; 5'-AGG TGC TAG AGG CCC TGC TA-3', 5'-GTG CAC AGA CAC CTT CCC AT-3'), c-myc (NM_012603; 5'-CTG GAG TGA GAA GGG CTT TG-3', 5'-CAG CAG CTC GAA TTT CTT CC-3'), c-jun (NM_021835; 5'-ACC AAG AAT TCC GTG ACG AC-3', 5'-CAA GGT CAT GCT CTG CTT CA-3'), and c-fos (NM_022197; 5'-CAT CGG CAG AAG GGG CAA AGT AGA G-3', 5'-TGC CGG AAA CAA GAA GTC ATC AAA G-3').…”
Section: Methodsmentioning
confidence: 99%
“…In the liver, the role of ACSL1 is not known, but changes observed in mRNA abundance generally coincide with reported changes in oxidative genes. For example, dietary supplementation with polyunsaturated fatty acids, overexpression of hepatocyte nuclear factor 4-a, and several PPARa agonists all increase the mRNA of ACSL1 as well as that of oxidative genes such as carnitine palmitoyl transferase-1 and acyl-CoA oxidase (9,(18)(19)(20). It seems likely that ACSL1 mRNA is under a complex regulatory control that is probably tissue specific.…”
Section: Discussionmentioning
confidence: 99%